Integrated case management between primary care clinics and hospitals for people with complex needs who frequently use healthcare services in Canada: A multiple-case embedded study. (June 2023) - Hudon, Catherine; Chouinard, Maud-Christine; Dumont-Samson, Olivier; Gobeil-Lavoie, Annie-Pier; Morneau, Jean; Paradis, Mélanie; Couturier, Yves; Poitras, Marie-Eve; Poder, Thomas; Sabourin, Véronique; Lambert, Mireille
Highlights: Leadership and support from all stakeholders lead to optimal implementation. Positive qualitative outcomes were observed when implementation occurred. Improved care integration and reduced ED visits were observed with full implementation. Abstract: Introduction: Case management (CM) is recognized to improve care integration and outcomes of people with complex needs who frequently use healthcare services, but challenges remain regarding interaction between primary care clinics and hospitals. This study aimed to implement and evaluate an integrated CM program for this population where nurses in primary care clinics worked with a hospital case manager. Methods: A multiple embedded case study was conducted in the Saguenay-Lac-Saint-Jean region (Québec, Canada), in four dyads including a clinic and a hospital. Mixed data collection included, at baseline and 6 months, interviews and focus groups with stakeholders, patient questionnaires (patient experience of integrated care and self-management), and emergency department (ED) visits in the previous 6 months. Results: Integrated CM implementation was optimal when all stakeholders provided collective leadership, and were supportive of the program, particularly the physicians. The 6-month program enabled the observation of positive qualitative outcomes in most clinic-hospital dyads where implementation occurred. Full implementation was associated with improved care integration. Discussion and conclusion: Integrated CM between primary care clinics and hospitals is a promising innovation to improve care integration for people with complex needs who frequently use healthcare services. Collective leadership and physicians' buy-in to integrated CM are important to foster the implementation.